Perbandingan Beton Dengan Menggunakan Portland Composite Cement Dan Ordinary Portland Cement - Vinansius Ponco; Jonie Tanijaya; Olan Jujun Sanggaria (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
Cement is the basic material for making concrete that can be used as a hydraulic binder. There are various types of cement including OPC and PCC cement. The problem now is that there is no technical data that can be used as a reference in determining the proportion of the mixture. Examples of cement are obtained from the same factory. namely PT. Semen Tonasa, South Sulawesi with an amount of 78.96 kg of cement for each type of cement. From the results of laboratory tests, it was found that the data on the comparison of concrete using OPC and PCC cements had different data on the of OPC cement is 3.726 Mpa and PCC cement is 3.223 Mpa and for testing the modulus of elasticity of OPC cement is 19371.316 Mpa and PCC cement is 17579.182 Mpa. The test results have met the standard for structural concrete with the same water-cement factor.